RANCANG BANGUN SMART CLOSED HOUSE PADA PETERNAKAN AYAM BROILER - Angga Dwipradipta, A A Gede; Dwija Ary Putra, I K J; Ardana, I P; Raka Agung, I G A P (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUM, 2024)
This research aims to enhance the growth performance of broiler chickens through the implementation of a smart closed house system. The prototype coop, with dimensions of 150 cm x 80 cm x 50 cm, has been successfully realized by integrating DHT22 and MQ135 sensors with exhaust fan and water pump actuators. The system is controlled by ESP32 DEVKIT, Long Range (LoRa) communication, and the Internet of Things (IoT). Collected data is sent to the Firebase and can be accessed through an Android application. Testing demonstrates that the sensors and actuators operate according to changes in temperature, humidity, and ammonia gas conditions inside the coop. LoRa communication testing involves sending sensor data (temperature, humidity, and ammonia gas) at distances of 1, 10, 100, 300, 500, and 600 meters. From the testing of LoRa transceiver data transmission, a character loss percentage of 0% is observed at 10 meters, while at 100 meters, there is a character loss percentage of 17.64%. Integration of data into Firebase is successful and displayed through the MIT App Inventor application on Android devices. Testing of chicken weight data indicates an increase in broiler chicken weight in the smart closed house coop compared to secondary data from conventional closed house coops. The testing period spans from day 7 to day 21 of the chicken's age. The highest recorded weight is 1031 grams, with the average weight for all chicken samples at the age of 21 days being 940 grams, 2.84% higher than the standard data from conventional closed house coops.